The ratio of the rational and irrational in the design of aesthetic environment - Tkachuk G. A. (Interactive science, 2019)
the article describes the use of designers in the process of preparation at the Department of Environmental Design of the Saint Petersburg Stieglitz State Academy of Art and Design unique method of preparing students for the discipline of «design». The method is based on a combination of rational and irrational approaches to work on the project. The specificity of the irrational approach to work on the creation of an artistic image of an object is described. and artistic concept. The process of searching for an artistic image of an object is analyzed. The artistic image and its value in the work on the project.
Keywords: образовательный процесс; художественный образ; композиция; проектирование; социальная среда; общественное сознание; educational process; rational; design; composition; social consciousness; artistic image; social environment; проектная концепция; рациональное; иррациональное; интеллектуальные модели; художественное моделирование; мечтательное состояние; материальный продукт; design concept; irrational; intellectual models; artistic modeling; dreamy state; material product